Them That Believe : The Power and Meaning of the Christian Serpent-Handling Tradition - Hood, Ralph W., Jr., 1942- (Book collections on Project MUSE., 2008)
Explores the religious practice of serpent handling in churches of Alabama, Georgia, Tennessee, Kentucky, North Carolina, and West Virginia. This book provides an analysis of this phenomenon from historical, social, religious, and psychological perspectives. It deals with the near-death experiences of individuals who were bitten but survived.